The Effect of Digital Flipbook Media on Improving Science Literacy on Human Digestive System Materials Among Elementary School Students - Rahma Maulina Hartomo; Wati Sukmawati (Jurnal Penelitian Pendidikan IPA, 2024)
This research aims to compare the effectiveness of two learning approaches in enhancing students' scientific literacy skills at the secondary school level. The methods employed were quasi-experimental with two groups: an experimental group applying Project-Based Learning (PjBL) using flipbook media, and a control group implementing conventional learning using PowerPoint media. Data were gathered through pretests and posttests administered to both groups. The findings revealed that the experimental group experienced a significant improvement in scientific literacy skills compared to the control group. The percentage of students who showed an increase in posttest scores in the experimental group (81.48%) was higher than that in the control group (53.57%). Data analysis also indicated lower result variability in the experimental group, highlighting consistency in learning effectiveness. Based on the research findings, the importance of interactive and contextual learning approaches in facilitating students' understanding of scientific concepts, with PjBL and flipbook media being more effective methods, is emphasized. The contribution of this research lies in providing a deeper understanding of the influence of learning methods and media on students' learning outcomes, with direct implications for teaching practices in schools